Literary cultures in history : reconstructions from South Asia - Pollock, Sheldon I. (Philip E. Lilienthal book., 2003)
A grand synthesis of unprecedented scope, Literary Cultures in History is the first comprehensive history of the rich literary traditions of South Asia. Together these traditions are unmatched in their combination of antiquity, continuity, and multicultural complexity, and are a unique resource for understanding the development of language and imagination over time. In this unparalleled volume, an international team of renowned scholars considers fifteen South Asian literary traditions--including Hindi, Indian-English, Persian, Sanskrit, Tibetan, and Urdu--in their full historical and cultural variety.The volume is united by a twofold theoretical aim: to understand South Asia by looking at it through the lens of its literary cultures and to rethink the practice of literary history by incorporating non-Western categories and processes. The questions these seventeen essays ask are accordingly broad, ranging from the character of cosmopolitan and vernacular traditions to the impact of colonialism and independence, indigenous literary and aesthetic theory, and modes of performance. A sophisticated assimilation of perspectives from experts in anthropology, political science, history, literary studies, and religion, the book makes a landmark contribution to historical cultural studies and to literary theory in addition to the new perspectives it offers on what literature has meant in South Asia.(Available in South Asia from Oxford University Press--India).